THE EFFECT OF RESPIRATORY RELAXATION WITH DHIKR TOWARDS REDUCING ANXIETY IN STUDENTS - Mei Dwi Yanti; Winda Agustina Anggraini; Siti Saluna Nurhalizah; Kartika Cantamala; Sunarsih (CV. Doki Course and Training, 2023)
Breathing relaxation with remembrance is one way to provide physical and psychological calm to humans. The purpose of this study was to determine the effect of breathing relaxation with dhikr on reducing student anxiety. The hypothesis of this study: there is a significant decrease in anxiety before and after the intervention. This experimental research design is a one group pretest posttest design. Collecting data using an anxiety scale. Based on the results of the student pre-test, the highest score data was 73 and the lowest score was 37 with an average of 52.33. Based on student post-test results, the highest score data was 54 and the lowest score was 37 with a class average of 45.47. Calculation of all research data using the computer program SPSS for windows. Thus, it can be concluded that breathing relaxation with dhikr has an effect on reducing anxiety in new students of the Psychology Faculty of UIN Raden Fatah Palembang.